THE EFFECTIVENESS OF QUIZIZZ MEDIA TO IMPROVE STUDENT’S READING SKILLS IN NARRATIVE TEXT FOR ELEVENTH GRADE (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the effectiveness of Quizizz as an advanced educational tool for enhancing narrative text reading comprehension among eleventh-grade students. Using a pre-experimental design with a single group pre-test and post-test approach, the research involved 18 eleventh-grade students. Statistical analysis included normality tests, reliability assessment, homogeneity of variance testing, and paired samples t-tests to evaluate the intervention's effectiveness. Results demonstrated a significant improvement in students' reading comprehension abilities following the implementation of Quizizz, with a mean difference of 31.611 between pre-test and post-test scores (p < 0.001). The findings indicate that Quizizz functions as an effective educational resource for developing narrative reading skills among senior high school students, underscoring the potential value of gamified learning platforms in contemporary language education.